Adsorption Studies Of Heavy Metals On Activated Carbon Prepared From Agricultural Waste - Latiff, Muhamad Faizal Pakir Mohamed (2018)
Commercially available activated carbon (AC) is still considered expensive due to the use of non-renewable and relatively expensive starting material such as bituminous coal. Therefore, this study investigates the potential use of agricultural waste such as rubber seed coat (RSC) and corncob (CC) that available in Malaysia, as the precursor for the preparation of AC which can be applied for the removal of two types of heavy metal, which are Cu (II) and Zn (II) from aqueous solution. Physiochemical activation consisting of potassium hydroxide (KOH) impregnation plus carbon dioxide (CO2) gasification was used to prepare the ACs. The optimum preparation conditions of RSCAC-CU were found at activation temperature of 793 °C, activation time of 1h and KOH impregnation ratio (IR) of 2.46. As for RSCAC-ZN, the optimum preparation conditions were at activation temperature of 797 °C, activation time of 1h and IR of 2.61. Meanwhile, the optimum preparation conditions of CCAC-CU were found at activation temperature of 762 °C, activation time of 2.7h and IR of 3.25. For CCAC-ZN, the optimum preparation conditions were at activation temperature of 768 °C, activation time of 3h and IR of 3.5. All the activated carbons prepared were high BET surface area (>500 m2/g) and pore volume (>0.41 m3/g). RSCAC and CCAC demonstrated homogeneous and heterogeneous type pore structures, respectively. The effects of adsorbate initial concentration (10-100 mg/L), contact time, solution temperature (30-60 °C), solution pH (2-6), isotherms and kinetics of the adsorption systems were evaluated through batch adsorption test. The Cu (II) and Zn (II) adsorption uptakes increased with increasing initial concentration and optimum contact time. Adsorptions of Cu (II) and Zn (II) on all ACs were best fitted by the Freundlich isotherm model. Adsorption kinetics of Cu (II) and Zn (II) followed pseudo-second-order on all the ACs. Fixed bed study showed that the exhaustion period for Zn (II) was greater than Cu (II) and the increase in bed heights resulted in higher exhaustion period.